Antiviral Efficacy of the Anesthetic Propofol against Dengue Virus Infection and Cellular Inflammation. (1st April 2021) - Shen, Ting-Jing; Chen, Chia-Ling; Jhan, Ming-Kai; Tseng, Po-Chun; Satria, Rahmat Dani; Hsing, Chung-Hsi; Lin, Chiou-Feng
Abstract : Propofol, 2, 6-diisopropylphenol, is a short-acting intravenous sedative agent used in adults and children. Current studies show its various antimicrobial as well as anti-inflammatory effects. Dengue virus (DENV) is an emerging infectious pathogen transmitted by mosquitoes that causes mild dengue fever and progressive severe dengue diseases. In the absence of safe vaccines and antiviral agents, adjuvant treatments and supportive care are generally administered. This study investigated the antiviral effects of propofol against DENV infection and cellular inflammation by using an in vitro cell model. Treatment with propofol significantly inhibited DENV release 24 h postinfection in BHK-21 cells. Furthermore, it also blocked viral protein expression independent of the translational blockade. Propofol neither caused inhibitory effects on endosomal acidification nor prevented dsRNA replication. Either the proinflammatory TNF- α or the antiviral STAT1 signaling was reduced by propofol treatment. These results provide evidence to show the potential antiviral effects of the sedative propofol against DENV infection and cellular inflammation.